ANALISIS TINGKAT PROFITABILITAS PERBANKAN (Studi Kasus pada PT Bank Pembangunan Daerah Jawa Timur Tbk Periode 2007-2014) - Ariani, Falentina Dwi; Satria, Dias (Jurnal Ilmiah Mahasiswa FEB, 2016)
Economic development in a country, can not be separated from the banking contribution which is the efforts of the banks contributed in fundraising and distribution of funds services through credit. Performance of a bank is required in this case, because of the good performance of the bank will raise the interest of investors to use bank services. One of the performance measurement can bebe with bank profitability. Furthermore, the profitability ratio used is Return on Assets (ROA) for the ratio has taken into account the profit made by a bank as a whole. The study was conducted at PT Bank Pembangunan Daerah Jawa Timur Tbk during 2007-2014. The method used in this research is multiple linear regression analyzes were then performed of test the classical assumption and further test the hypothesis. The results obtained in this study indicate that the variable BOPO and inflation have significantly negative effect on bank profitability (ROA). While the variable size and NIM have significantly positive effect on bank profitability (ROA). Then the variable low-cost funds, LDR, and CAR show positive results but their effect is not significant on bank profitability (ROA). Keywords: low-cost funds, LDR, CAR, Size, BOPO, NIM, Inflation, Profitability, ROA